Electronic User Authentication Key for Access to HMI/SCADA via Unsecured Internet Networks - Amer Tahseen Abu-Jassar; Hani Attar; Yevsieiev, V.; Ayman Amer; Demska, N.; Ashish Kr. Luhach; Lyashenko, V. (Hindawi, 2022)
This paper discusses the development of new hardware and software for protecting access to HMI/SCADA systems via Unprotected Internet Networks (UPN), mainly when working remotely with confidential information. Based on the analysis carried out, it is shown that the existing vulnerabilities can be exploited by cybercriminals to steal passwords and user authentication logins. Modern protection technologies based on the OTP method have been investigated. Moreover, a new concept of information security for user authentication in UPNs when working with information remotely is proposed. The structure of the electronic key and the connection diagram based on the selected hardware modules have been developed. In addition, the two-level user identification algorithms and the firmware program code for the ATmega32U4 microcontroller are considered. Finally, to show the reliability and stability of the of the developed electronic user authentication key against any unexpected software hacking, a number of experiments have been performed.
Keywords: Industry 4.0; Electronic Key; HMI/SCADA; Unprotected Internet Networks